Relationship between eHealth Literacy and Health Promoting behaviors among nursing students - Leana Flordeliza Agapito; Alyssa Marielle Cortez; Auryjeena Fong; Christiene Jann Sanchez; Kathyrine Calong Calong; Carissa Juliana Balaria; Gil Soriano (Jurnal Keperawatan Padjadjaran, 2024)
Background: Utilizing health literacy is important in establishing knowledgeable health advancements and practices, which can become deterrents to promoting a healthy lifestyle. Technological advancements improve health information availability and accessibility that potentially affect the users’ proficiency and their capability in applying the accessed health information. However, accessing health information via IT for health promotion requires e-health literacy. Purpose: The objective of the study is to determine the relationship between eHealth literacy and health-promoting lifestyle behaviors among nursing students. Methods: Descriptive-correlational study was applied to 131 nursing students recruited through a purposive sampling method from a nursing school in Philippines. The researchers adopted original English version of the e-Health Literacy Scale and Health-Promoting Lifestyle Profile II (HPLP) to collect the data.  The gathered data were analyzed using descriptive analysis; frequency, percentage, mean, standard deviation, and test the correlation using Pearson's r correlation. Results: A total of 131 nursing students were employed in the study with a mean age of 20.14 (±1.22). Participants were female (71.8%) and are Level 1 students (44.3%) The mean of the total sum score for eHealth literacy was 31.24 (±4.30) while the over-all item mean was 3.92 (±0.54). On the other hand, the health-promoting behavior has a mean score of 2.43 (±0.43) while its subscales have a mean score of 2.46 (±0.45) for nutrition, 2.45 (±0.62) for physical activity, and 2.39 (±0.47) for health responsibility. It was found that eHealth literacy had a significant relationship with the students’ health-promoting behavior (r=0.245, p=0.005). Hence, students who have a high level of eHealth literacy are more inclined to perform healthy behaviors. Conclusion: The results of this study showed that the development of strategies to improve the e-health literacy of nursing students may contribute to the maintenance of their health-promoting behaviors. Identified intervention strategies based on eHealth literacy are needed to encourage healthy practices, which may reduce risks of illnesses due to unhealthy lifestyle behaviors among nursing students.